Analisis Aktivitas Perawatan Mandiri Dan Status Pengontrolan Tekanan Darah Pada Pasien Hipertensi Di Komunitas Pesisir - Yulia Devi Putri; Nursyirwan Effendi; Adang Bachtiar; Harnavi Harun (Jurnal Ners, 2026)
Maritime communities possess unique socio-cultural and environmental characteristics that contribute to low success rates in blood pressure control. Self-care is a key factor in hypertension management; however, its implementation within fishing communities is often hindered by local work patterns and lifestyles. Objective this study aimed to analyze the relationship between self-care activity dimensions and blood pressure control status among hypertensive patients in the coastal area of ​​Batam City. Methods a cross-sectional study design was employed, involving 237 respondents diagnosed with hypertension selected via consecutive sampling. The sample size was calculated using the Lwanga & Lemeshow formula for two proportions. Data were collected using the H-SCALE questionnaire—which had undergone translation and validity/reliability testing—and through standardized blood pressure measurements. Data analysis utilized the Chi-square test (p < 0.05) and Odds Ratio (OR). Results the majority of respondents were male (60.8%) and primarily employed as fishermen (52.7%). A total of 74.3% of respondents had uncontrolled blood pressure. Statistical analysis revealed significant associations between uncontrolled blood pressure and non-adherence to medication (p = 0.001; OR = 3.12), non-adherence to a low-salt diet (p = 0.008; OR = 2.24), and poor stress management (p = 0.003; OR = 2.58). Conclusion self-care activities within the maritime community remain low, contributing to high rates of uncontrolled hypertension. Integrated community nursing interventions that are sensitive to the dynamics of coastal life are required.